Analisis Variasi Lebar Magnet pa ANALISIS PENGARUH LEBAR MAGNET NEODYMIUM PADA KINERJA PERMANENT MAGNET SYNCHRONOUS GENERATOR (PMSG) 12 SLOT 8 POLE MENGGUNAKAN SOFTWARE MAGNET INFOLYTICA - Muhammad Afdhal Izzati; Refdinal Nazir; Anna Cyntia Pahsa De Yudanur; Maulana Naseem Hamed (BRILIANT: Jurnal Riset dan Konseptual, 2026)
Permanent Magnet Synchronous Generator (PMSG) with 12 slots 8 poles, using Magnet Infolytica software. The main focus of the research is to evaluate the impact of changes in the width of the permanent magnet (32 mm to 52 mm) on electromagnetic characteristics, such as current, voltage, torque, input power, output power, and energy conversion efficiency. Simulations were carried out at a rotational speed of 750 rpm with a resistive load of 70 Ohm. The results showed that increasing the width of the permanent magnet had a positive impact on the performance of the PMSG, the best generator at a variation of the magnet width of 44 mm which had an efficiency of 88.6% with a current of 8.9 A, a voltage of 565.97 V, a torque of -66.08 N/m, an input power of 5189.79 Watts, and finally an output power of 4598.67 Watts. These findings are expected to be a reference in designing an optimal PMSG for small to medium-scale renewable energy power generation applications, especially in Wind Power Generation (PLTB) systems.